A qualitative study researching the perceived impacts of Biophilic Design on building occupant health and well-being within a corporate setting. - Middleton, Travis (The IIE, 2021)
Background to the study: This paper showcases an Interior Design focused qualitative study concerned with investigating the impacts of Biophilic Design on building occupant health and well-being within a corporate work setting and conduct an inquiry into the Biophilia inspired Elaleni Coastal Forest Estate office on the North Coast of South Africa. Main argument: Elements of Biophilia within a working environment largely benefits the built environment in terms of Indoor Environmental Quality (I.E.Q) and as a result has positive outcomes on well-being standards for the building occupants thus leading to improved levels of mental / physical health, happiness and well-being. Problem: The identified problem was focused on the issue of poorly designed corporate workspaces inducing conditions of Sick Building Syndrome (S.B.S) as a result of the built environment and thus negatively impacting employees’ standards of productivity, performance, comfort, mental / physical wellness and job satisfaction. Data collection method and reasoning: Questionnaires was the choice of data collection as a result of geographical constraints between participants and the researcher as well as time constraints, this method allowed the data to easily be compared, analysed, interpreted, visualised and represented for the study. Most significant findings and contribution: The relationship between Biophilia, I.E.Q and human health largely interlink, the study found that Biophilia positively impacts interior design and occupants’ wellness levels - contributing towards available literature relating to Biophilic Design, I.E.Q and Sick Building Syndrome in corporate work settings
Keywords: Mental health; Mental well-being; Physical health; Sick Building Syndrome (S.B.S); Employee performance; Job satisfaction; Corporate